Please join us : a novel - McKenzie, Catherine (Atria Books, 2022)
"At thirty-nine, Type-A Nicole Muller's life is on the rocks. Her once brilliant law career is falling apart. Her friends are all having their last-minute babies before they turn forty and she remains childless. She loves her husband, Daniel, but they're soon to be forced out of the family apartment they've rented for years. Shortly after a warning from her senior partners, she's shocked when she receives an email from an exclusive women's networking group, Panthera Leo. Membership is anonymous, but every women is a successful professional. And although Dan worries this group might be a cult, Nicole signs up for their retreat in Wyoming. Once there, she meets the other women who will make up her Pride. A CEO, an actress, a finance whiz, a congresswoman: Nicole can't believe her luck. The founders are a famous musician and the founder of a massive wellness empire. They explain the group's core philosophy: they're a girl's club in a man's club world. Nicole is all in. And when she gets back home, she soon sees dividends. Her new network quickly provides her with clients that help her relaunch her career, and a great apartment too. The favors she has to provide in return seem benign. But then she's called to the congresswoman's apartment late at night where she's pressed into helping her cover up a crime. And suddenly Dan's concerns that something more sinister is at play seem all too relevant"--